Changes of telomere status with aging: An update. (March 2016) - Ishikawa, Naoshi; Nakamura, Ken‐Ichi; Izumiyama‐Shimomura, Naotaka; Aida, Junko; Matsuda, Yoko; Arai, Tomio; Takubo, Kaiyo
Abstract : Accumulated data have shown that most human somatic cells or tissues show irreversible telomere shortening with age, and that there are strong associations between telomere attrition and aging‐related diseases, including cancers, diabetes and cognitive disorders. Although it has been largely accepted that telomere attrition is one of the major causes of aging‐related disorders, critical aspects of telomere biology remain unresolved, especially the lack of standardized methodology for quantification of telomere length. Another frustrating issue is that no potentially promising methods for safe prevention of telomere erosion, or for telomere elongation, have been devised. Here, we review several methods for quantification of telomere length currently utilized worldwide, considering their advantages and drawbacks. We also summarize the results of our recent studies of human cells and tissues, mainly using quantitative fluorescence in situ hybridization and Southern blotting, including those derived from patients with progeria‐prone Werner syndrome and trisomy 21, and several strains of induced pluripotent stem cells. We discuss the possible merits of using telomere shortness as an indicator, or a new marker, for diagnosis of precancerous states and aging‐related disorders. In addition, we describe newly found factors that are thought to impact telomere dynamics, providing a new avenue for examining the unsolved issues related to telomere restoration and maintenance.Geriatr Gerontol Int 2016; 16 (Suppl. 1): 30–42.